Interpreting Sustainability Signs In A Malang Hotel: A Semiosis Analysis Of Repeated Guest Experiences - Situmorang, Benita; Prasetyo, Bambang Dwi; Wulandari, Maulina Pia; Syahri, Moch. (Journal of Indonesian Tourism and Development Studies, 2026)
The increasing implementation of sustainability practices in the hospitality industry reflects a commitment to environmental responsibility. However, sustainability symbols often serve as visual elements whose meaning is not fully understood by hotel guests. This study explores how guests' repeated experiences influence their interpretation of sustainability symbols at the Grand Mercure Malang Mirama Hotel. Using a qualitative research design, this study combines Peircean semiotic analysis with the photo elicitation method. The data consist of 20 sustainability-related signs identified through observation and in-depth interviews with 7 domestic guests who stayed for at least 2 nights. Data were collected through systematic observation, and interviews were analyzed using Peirce's triadic semiosis framework, with deductive and inductive reasoning to explore emotional, energetic, and ultimate interpretants. Findings indicate that sustainability indicators, such as eco-friendly symbols, energy efficiency, and documented environmental activities, are more effective at driving shifts toward energetic and ultimate interpretants. Conversely, symbolic signs such as sustainability certifications trigger emotional responses and visual impressions, often leading to interpretive ambiguity. This study contributes to the fields of sustainability communication and hospitality studies and expands Peirce's semiotics in the context of sustainability in the hospitality industry in Indonesia.